The spectre of terrorism and the stock market - Alan J. Hanna; John D. Turner; Clive B. Walker (Queen's University Centre for Economic History (QUCEH), 2022)
Terrorism is a major issue in the 21st century. In this paper we examine the effect of terrorism on the stock market. We go beyond previous studies to explore the spectre of terrorism on the market rather than terrorist activities. Using a narrative-based approach à la Shiller (2019), we find that the spectre of terrorism during the Northern Ireland Troubles reduced returns and increased volatility on the UK stock market.
Keywords: C00; E44; G12; G40; N24; 330; terrorism; stock market; returns; volatility; narratives